Reasons and Challenges of China’s Judicial Reforms - Hamid Mukhtar; Kashif Mahmood Saqib; Abdul Rasheed (Journal of Management Practices, Humanities and Social Sciences, 2021)
With the advancement of society, Chinese authorities have been undertaking mega reforms in judicial sector. As a result of judicial reformation, current state of Chinese Judiciary is one of the technologically advanced systems in the world, which is efficiently dispensing justice to the largest population in the globe. This research investigates the reasons behind Chinese Judicial reforms. Research demonstrates that although reforms in the judicial sector began later than the reforms in the other areas such as the political system and economy sectors, the pace of reforms in the judicial sector has been rapid as compared to other areas. Judicial reforms in China have been guided by the public’s demand for the transparent judicial system, international commitments of China and the party’s priority to undertake judicial reforms. Transformation of the Chinese economy from a planned economy to a market economy also required for the extensive reformation of the judicial system. Significantly, the Chinese determination to promote socialist rule of law with Chinese characteristics has further impacted the judicial reformation process. Judicial openness has become an essential condition for the promotion of the rule of law in China. Research in hand tries to figure out the reasons behind judicial reforms in China. Further, it has outlined the challenges on the way judicial reforms. Existing literature and official reports about judicial reforms have been consulted and analyzed to reach towards a conclusion. Research shows that various national as well as international actors influenced the reform process. This study gives an impartial view point on the topic which will help the readers to understand Chinese Judicial System.